Medical education – historic perspective and future challenges - Silva, Luiz Fernando Ferraz da; Baracat, Edmund Chada (Revista de Medicina, 2016)
The history of medical education is binded to the history of medicine itself once teach, learn and practice happens together. Since ancient times the role of the mentor / tutor is the key to practical learning. Over time, and particularly in the last 300 years, the medical knowledge expansion and new technologies incorporation brought drastic changes in medicine and, therefore, in medical education but yet, the presence of one or many reference doctors in medical learning is still an important part of thousands of undergraduate students every year. In this period new concepts, new teaching techniques and use of multiple technologies including distance learning and simulation were included in several medical curricula. In this article we seek to briefly present the key events of the evolution of medical education including some particularities of medical education in Brazil and at USP School of Medicine, as well as point out the challenges for the ongoing century.